Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/aws2.1148
|View full text |Cite
|
Sign up to set email alerts
|

UV LED water disinfection: Validation and small system demonstration study

Abstract: What initially drew you to water research?My dedication to protect and provide water is ingrained by my Central Appalachian heritage, where my neighborhood creek was polluted by sewage and irresponsible natural resource extraction. My lifetime enjoyment of the outdoors-especially water -drove me to find solutions for these environmental problems. From my earliest undergraduate research experience studying slow sand filters for microbial water treatment in developing countries, I was captivated by the intersect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Ammonia nitrogen and total phosphorus were also not reduced significantly; however, nitrate nitrogen was reduced by an average of 41.4% (±40.5). Previous studies involving WFMF membrane bioreactors showed statistically significant reduction of ammonia nitrogen, nitrite nitrogen, phosphate, and other nutrients; however, those studies involved biological membrane growth in which the biomass performed a nitrification step, whereas the WFMF in this study was primarily a physical removal process [26,48]. UVT 254 improved from an average of 33.1% (±15) to an average of 52.5% (±14) after WFMF filtration.…”
Section: Domestic Wastewatermentioning
confidence: 71%
See 3 more Smart Citations
“…Ammonia nitrogen and total phosphorus were also not reduced significantly; however, nitrate nitrogen was reduced by an average of 41.4% (±40.5). Previous studies involving WFMF membrane bioreactors showed statistically significant reduction of ammonia nitrogen, nitrite nitrogen, phosphate, and other nutrients; however, those studies involved biological membrane growth in which the biomass performed a nitrification step, whereas the WFMF in this study was primarily a physical removal process [26,48]. UVT 254 improved from an average of 33.1% (±15) to an average of 52.5% (±14) after WFMF filtration.…”
Section: Domestic Wastewatermentioning
confidence: 71%
“…Reduction equivalent dose (RED) and log inactivation were modeled for a single challenge microorganism based on the combined variable approach presented by Wright et al [47] and Hull et al [48] and described in Equation ( 1):…”
Section: Combined Variable Approach To Red and Log Inactivation Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Simple and economical abovementioned factors, in favour of the reported micro-device (calculated-cost ¼ 5 USD per unit, approx.) reason it to be a 5 to 10 times costeffective substitute in comparison to any UV-C based waterdisinfection unit (present in several existing commercial devices), with comparable sterilization capability [9][10]. Hence, the reported device may be considered as a compact, efficient, as well as, low-cost solution for any similar purpose.…”
Section: Resultsmentioning
confidence: 92%